Mangiferin attenuates blast-induced traumatic brain injury via inhibiting NLRP3 inflammasome. (1st June 2017) - Fan, Kaihua; Ma, Jie; Xiao, Wenjing; Chen, Jingmin; Wu, Juan; Ren, Jiandong; Hou, Jun; Hu, Yonghe; Gu, Jianwen; Yu, Botao
Abstract: There is growing evidence that Mangiferin possess therapeutic benefit during neuroinflammation on various brain injury models due to its anti-inflammatory properties. It is reported that inflammatory plays a crucial role in the pathogenesis of secondary injury induced by the blast-induced traumatic brain injury (bTBI). However, the role of mangiferin in bTBI is yet to be studied. In our study, the potential effect of mangiferin in the duration of bTBI was examined first. Fortunately, the amelioration of cerebral cortex damage was found in rats suffering bTBI after mangiferin administration. Furthermore, the detail mechanism of mangiferin's beneficial actions in bTBI was also studied. The results revealed that mangiferin might alleviate brain damage in rats with bTBI by inhibiting the NOD-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome activation, which was accompanied by mangiferin's inhibition of oxidative stress and pro-inflammatory cytokines production. Therefore, this research allows us to speculate that, for first time, NLRP3 is involved in the anti-inflammatory effect of mangiferin in the cerebral cortex, and mangiferin could be a potential therapy drug for bTBI. Graphical abstract: Mangiferin exhibit neuroprotective effects in rats suffering blast-induced traumatic brain injury together with suppressing the activation and expression of NLRP3 inflammasome, which would be the possible mechanism. Highlights: MG be a new therapeutic drug for bTBI. MG act as an antagonist of NLRP3 in bTBI. The possible mechanism involved in MG suppressing NLRP3 is ROS-TXNIP pathway.